Pilot Project on Concentration and Distribution Measures for a Selected Set of Financial Soundness Indicators - Crowley, Joseph; Koukpamou, Plapa; Loukoianova, Elena; Mialou, Andre (Washington, D.C. : International Monetary Fund, 2016)
This paper reports the main findings of a pilot project launched in July 2014 by the IMF's Statistics Department to test augmenting the IMF's financial soundness indicators (FSIs) with concentration and distribution measures (CDMs) to capture tail risks, concentrations, variations in distributions, and the volatility of indicators over time that simple averages can miss. Volunteer participants reported a trial set of CDMs to assess analytical usefulness and identify concerns such as confidentiality and reporting burden. The results of the pilot suggests that CDMs can help detect financial sector risks, justifying the additional reporting burden but that further input from participating countries and potential data users should be sought; indeed further refinement of the reporting requirements and the CDMs themselves may be needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CDM Dataset; CDM; Core FSIs; Quartile; WP